Empowerment of mushroom farming communities with iot based monitoring in Karang Kepanjen, Sleman - Iswanto Suwarno; Nia Maharani Raharja; Alfian Maarif; Muhammad Abdus Shomad; Adhianty Nurjanah; Dhiya Uddin Rijalusalam; Rachmad Andri Atmoko; Irfan Ahmad; Israa Al_barazanchi; Sashikala Mishra (Peneliti Teknologi Teknik Indonesia, 2021)
Mugi Barokah “Mushroom Farmer UKM” is located in an agricultural area in Sleman Regency, precisely in Karang Kepanjen Hamlet, Trimulyo Village, Sleman District, Sleman Regency, Yogyakarta Special Region has been conducting mushroom cultivation activities since 2009. Mugi Barokah mushroom cultivation is led by Mr. Agus Arif Effendi. Actually, these SMEs have a large enough market opportunity for mushroom cultivation. However, this opportunity brings consequences and problems, namely the lack of a touch of innovation from the mushroom temperature and humidity monitoring system. The mushroom cultivation treatments they do include adjusting the intensity of the light by installing mosquito nets, adjusting the humidity of the mushroom room by spraying with water and to determine the temperature and humidity in the mushroom room by visual checking. Information about some of the problems faced by mushroom cultivation must of course be addressed as soon as possible as a solution for developing mushroom cultivation businesses. The team that proposes service as part of the community who happens to be involved in the world of education, feels compelled to help provide solutions to the problems faced by the mushroom farmer's business. Through this proposed science and technology activity program and based on the needs analysis that has been carried out, the service team tries to offer solutions to these problems with a touch of science and technology, namely through the main activity of designing remote mushroom monitoring with IoT technology. Temperature monitoring and control tool for mushroom fungus using an Arduino microcontroller, a DH11 sensor for temperature and humidity sensors and using IOT technology for remote monitoring. By using this tool the mushroom fungus can be monitored and controlled remotely using the Android application.